Inventarisasi Bintang Laut (Asteroidea) di Zona Intertidal Pantai Sopapei Kabupaten Maluku tengah - Mairuhu, Ziepora Veronica; Leiwakabessy, Jusuf; Mailoa, Meigy Nelce (Biosel Biology Science and Education, 2024)
Indonesia is one of the largest archipelagic countries in the world with 13 thousand islands, its strategic location and long coastline make Indonesia a haven for many marine life. It causes the richness of flora and fauna in it is high and diverse. The diversity of marine animals includes the starfish (Asteroidea). The aim of study was to inventory several species of starfish (Asteroidea) that was found in the waters of located in Suli Village, Central Maluku Regency. The sampling method used in this study was random sampling, in which the sample was taken randomly by exploring the waters of Sopapei. Based on the results of study, it was obtained three species starfish, namely Protoreaster nodosus, Linckia laevigata, and Archaster typicus. Keywords Asteriodea, Star Fish, Intertidal Zone